Autotransplantation of cryopreserved ovarian tissue in oncological patients: recovery of ovarian function. (March 2014) - Fabbri, Raffaella; Pasquinelli, Gianandrea; Magnani, Valentina; Macciocca, Maria; Vicenti, Rossella; Parazza, Isabella; Paradisi, Roberto; Battaglia, Cesare; Rossi, Stefania; Venturoli, Stefano
ABSTRACT: : Aim: To present preliminary results of autotransplantation of cryopreserved ovarian tissue performed at Sant'Orsola-Malpighi Hospital, Bologna, Italy.Materials & methods : Orthotopic transplantation was performed in two women with colorectal and breast cancer, and heterotopic transplantation was performed in one Hodgkin's lymphoma woman. The presence of micrometastasis in the ovarian tissue was checked, and morphological features of ovarian tissue were evaluated before transplantation. Ovarian function was monitored by hormonal and ultrasound-color Doppler examination after transplantation.Results : In all three women, no micrometastasis was found; light and transmission electron microscopy showed well-preserved thawed ovarian tissue. Ovarian function recovery was observed 2–4 months after transplantation. Spontaneous menstrual cycles occurred in two women with normal follicular densities. No periods occurred in the woman with low follicular density at the time of tissue collection.Conclusion: Ovarian tissue cryopreservation and transplantation is a promising approach for preserving ovarian function in women with cancer.